Complex Analysis And Applications - Proceedings Of The 13th International Conference On Finite Or Infinite Dimensional Complex Analysis And Applications - Hasi Wulan, Yuefei Wang, Shengjian Wu (World Scientific Publishing Company, 2006)
This valuable collection of articles presents the latest methods and results in complex analysis and its applications. The present trends in complex analysis reflected in the book are concentrated in the following research directions: Clifford analysis, complex dynamical systems, complex function spaces, complex numerical analysis, qusiconformal mapping, Riemann surfaces, Teichmüller theory and Klainian groups, several complex variables, and value distribution theory.Sample Chapter(s)Chapter 1: Complex Boundary Value Problems in a Quarter Plane (490 KB)Contents:Complex Boundary Value Problems in a Quarter Plane (H Begehr & G Harutyunyan)A Change of Scale Formula for Wiener Integrals of Unbounded Functions over Wiener Paths in Abstract Wiener Space (K S Chang et al.)Qp-Spaces: Generalizations to Bounded Symmetric Domains (M Engliš)Order of Growth of Painlevé Transcendents (A Hinkkanen & I Laine)A Remark on Holomorphic Sections of Certain Holomorphic Families of Riemann Surfaces (Y Imayoshi & T Nogi)α-Asymptotically Conformal Fixed Points and Holomorphic Motions (Y Jiang)Uniqueness Theory of Meromorphic Functions in an Angular Domain (W Lin & S Mori)On Nevanlinna Type Classes (N Sukantamala & Z Wu)On Non-Existence of Teichmüller Extremal (G Yao)The Möbius Invariance of Besov Spaces on the Unit Ball of Xn (K Zhu)and other papersReadership: Researchers and graduates in complex analysis.